The effect of systemic lycopene supplementation on non-surgical periodontal therapy outcomes: A clinical trial - Fahimeh Rashidi Maybodi; Faezeh Sadeghi Heris (BDJ Open)
Abstract Introduction Some recent studies have suggested that antioxidants, particularly lycopene, may improve periodontal treatment outcomes. However, conflicting past results regarding its effects highlight the need for further research. This study aimed to evaluate the clinical effects of oral lycopene supplementation as an adjunctive therapy in nonsurgical periodontal treatment for patients with periodontitis. Methods In this parallel clinical trial, 42 patients aged 25 to 55 with moderate to severe periodontitis and no recent history of periodontal treatment were randomly assigned to two groups after matching for mean age, sex, periodontal disease severity, and antioxidant capacity. One group received lycopene supplementation (15 mg/day) and phase I periodontal therapy. In contrast, the other group received a placebo (containing 1 g of corn starch) and phase I periodontal therapy. Periodontal parameters, including probing depth (PD), clinical attachment loss (CAL), and bleeding index (BI), as well as serum Malondialdehyde (MDA) levels, were assessed at baseline and after two months. Results Both groups showed significant improvements in periodontal parameters after two months. However, the lycopene group demonstrated greater reductions in probing depth (P = 0.009), clinical attachment loss (P = 0.015), bleeding index (P = 0.237), and MDA levels (P = 0.199) compared to the placebo group, confirming its positive effect in reducing oxidative stress and inflammation associated with periodontitis. Conclusion Oral lycopene supplementation was associated with better clinical outcomes than the placebo as an adjunct to nonsurgical periodontal therapy. It may be recommended as part of a periodontal treatment plan to enhance periodontitis management.